Theory of financial risks : from statistical physics to risk management - Bouchaud, Jean-Philippe; Potters, Marc (Cambridge University Press, 2000)
Summarizes recent theoretical developments inspired by statistical physics in the description of the potential moves in financial markets, and its application to derivative pricing and risk control. Of interest to physicists, quantitative analysts in financial institutions, risk managers and graduate students in mathematical finance.